Zjazd śpiewaczy połączony z konkursem chórów. (Gdańsk : [s.n.], 1947)
Afisz z programem zjazdu, który miał miejsce 26.10.1947 r. w Gdańsku.
Keywords: Chóry -- Polska -- 1945-1970 -- druki ulotne; Życie muzyczne -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła